Potential Provinces in Papua New Guinea for Rice Farming - Mohamed Aezeden; Goru Donovan; Samanta Sailesh (E3S Web of Conferences, 2024)
Papua New Guinea has plenty of land with suitable agro-climatic conditions for rice farming, but despite this, the country still needs to import rice to meet the demands of its rapidly growing population and urbanization. To address this issue, a research project was undertaken to create a realistic scope and map of areas within each province of Papua New Guinea that are suitable for rice production, using Remote Sensing (RS) and Geographic Information System (GIS) techniques. The study included nineteen regions of Papua New Guinea. A digital surface model was used to determine the suitability of each area for large-scale rice farming, based on climate, soil factors, and topography. The Erdas Imagine v-11 model builder was used to create a critical model for the suitability of rice mapping. Each province was classified into five classes based on the suitability of the land for rice farming. The results showed that approximately 14% of the land in Papua New Guinea is exceptionally suitable for rice farming. Eight provinces (Central, East Sepik, East New Britain, Morobe, Madang, Milne Bay, West New Britain, and Western Province) were identified as having large-scale land suitable for rice production and were evaluated accordingly.